Genetic divergence and PCA for salinity tolerance in rice at reproductive stage - Kumar, Awaneet; Mandal, A B; Sarangi, S K (ORYZA-An International Journal of Rice, 2018)
Rice (Oryza sativa L.) is one of the most significant cereal crops, about 3 billion people, nearly half the world’sÂ population; depend on rice for survival and it offers up to 80% of daily energy intake in most of the AsianÂ countries. Salinity is the second most constraints after drought and limits the rice production worldwide. In thisÂ context, study on genetic divergence for salinity tolerance is most important and accordingly an assessment hadÂ been done on the genetic diversity among 40 rice genotypes grown at CSSRI, RRS, Canning town, South 24-Â Pargana, W.B. in the soil salinity of 6 dS/m in two replications following randomized block design in plots of sizeÂ 1m Ã— 1m with spacing 20 cm Ã— 15 cm during rabi, 2013. The data were recorded on four reproductive growth stage characters viz., pollen viability, number of unfilled grains per panicle, number of filled grains per panicleÂ and grain yield per plant (g). All the forty genotypes showed differential performance with respect to the characters studied and had been grouped into 6 clusters.Cluster I comprised of highest i.e., 11 whereas ClusterÂ II contained lowest i.e., 3 number of genotypes.The value of intra-cluster distance ranged between 6.28 and 58.96 whereas the inter-cluster distance varied from 34.39 to 2238.47. Considering the cluster mean, cluster VÂ possessed the least value and cluster VI possessed the highest value for all the four characters.The relative increase of unfilled grain per panicle contributed the highest contribution (92.18%) followed by relativeÂ reduction in grain yield per plant (4.10%) and relative reduction in pollen viability (2.05%), respectively.Â Principal component analysis indicated that the three components, PC1, PC2 and PC3 could explain for a totalÂ of 98.110% of total variation. Among these, PC1, PC2 and PC3 explain for 90.077%, 5.584% and 2.449% of theÂ total variation respectively. The component score co efficients of PC1, PC2 having positive values for majority ofÂ the variables under study suggested major component among the 3PCs.The bi-plot of PC1 against PC2 revealedÂ considerable variation among genotypes in their response to salinity treatments where the genotype vectors ranged from 12 to 58 considering vector 1 and from -18 to 2 considering vector 2.